Original article Vital role of volume and number of needles in HDR brachytherapy (HDR-BT) of prostate cancer - Chicheł, Adam; Kanikowski, Marek; Skowronek, Janusz (Journal of Contemporary Brachytherapy, 2009)
Purpose: The quality of HDR-BT of prostate cancer depends on operator skills, anatomy, prostate volume and relation to surrounding tissues as well as previous diseases and treatments of a patient. There is a rare data available concerning the minimum number of needles and its influence on dose distribution, side effects and long-term outcome. The study is to determine the minimal prostate volume and minimum number of needles suitable for HDR-BT in order to obtain an implant of good quality. Material and methods: 181 patients with localized prostate cancer were treated with interstitial HDR-BT boost. 15 Gy from HDR-BT was administered after 50 Gy from EBRT. Clinical, volumetric and dosimetric data were collected. Treatment plans were divided into Group A, consisted of optimal treatment plans (P-D90 > 90%, P-V200 < 15%, U-D10 < 125%, U-Dmax < 160%, R-D10 < 85%) and Group B, with suboptimal plans. Results: The difference between two groups was statistically significant (p = 0.013) with regard to number of needles. There was no statistically significant difference concerning prostatic volume. Median number of inserted needles in the first and the second group resulted in 15 (range 9-18) and 13 (range 8-18), respectively. Differences were the most eminent in patients with prostate glands of small volume (< 20 cc). In the study, either the minimum number of needles nor minimal prostate gland volume were not clearly defined in terms of high probability of achieving a good quality implant. Conclusions: Larger volume and higher number of needles are related to an advanced probability of treatment plan with all DVC fulfilled. The minimum number of needles suggested is > 9, optimally ł 13. Furthermore, the minimal prostate volume recommended is > 12 cc, optimally ł 18 cc. The volume of insufficient size and/or small number of needles results in suboptimal treatment plans.